Effect Of Soy Milk Consumption On Breast Milk Flow Among Breastfeeding Mothers - Monica, Ica Fitria; Widiyanti, Septi; Ridwan, M. (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Breastfeeding is the process by which a mother nurtures and supports her child after childbirth. Factors that may hinder exclusive breastfeeding include engorged breasts, babies with short tongues, and insufficient breast milk supply. According to the 2023 Metro City Health Profile, out of 11 urban villages, the lowest breastfeeding coverage is in Karangrejo, at 50.3%. Failure to breastfeed can be caused by the mother's nutritional status before pregnancy, during pregnancy, and while breastfeeding. Mothers who do not breastfeed are at risk of developing various diseases or health problems, such as diabetes, overweight and obesity, breast cancer, uterine cancer, hypertension, and heart disease.Aim: The aim is to determine the effect of soy milk on the breast milk flow among breastfeeding mothers in the working area of Karangrejo Community Health Center.Methods: This is a quantitative research study with a pre-experimental research design, specifically a one-group pretest-posttest design. The total population in this study consists of 92 breastfeeding mothers with babies aged 0-6 months. The sample size is 38 respondents who were selected using purposive sampling technique and the Wilcoxon test was used for analysis.Results: Prior to the intervention, all respondents (100%) reported having difficulties with their breast milk flow. Following the intervention, 89.5% of respondents (34 individuals) reported an improvement in their breastfeeding experience, while 10.5% (4 individuals) did not experience this improvement. The Wilcoxon test indicated a p-value of 0.000.Conclusion: The study found that the consumption of soy milk has a positive effect on the smoothness of breast milk flow in breastfeeding mothers. It is recommended to provide information about the benefits of consuming soy milk for the smoothness of breast milk flow.Recommendation: Encourage mothers to consume soy milk to improve the smoothness of their breast milk flow.Keywords: Breast milk flow smoothness, soy milk